SOME FACTORS AFFECTING EXCLUSIVE BREASTFEEDING (EBF) AMONG MOTHERS IN DUTSIN-MA COMMUNITY OF KATSINA STATE, NIGERIA - Magaji, Kabir; Justin, Ezenkiri Nwankwo (PEOPLE: International Journal of Social Sciences, 2015)
This study investigated some factors affecting exclusive breastfeeding (EBF) among mothers in Dustin-ma community of Katina state, Nigeria with an intension to proffer lasting solution for effective EBF. Descriptive survey research design was used in this study. The population of the study was all mothers drawn from eleven political Wards of Dutsin-ma Local Government Area, Katsina State. A sample of 177 mothers was used, using cluster sampling technique. A self-developed questionnaire named EH- QEBF was used, using split-half method with the help of Spearman –Brown Prophecy Formula for reliability (0.76). Frequency counts and percentage were used to organize and present the demographic data of the respondents; t-Test was used to test the two hypotheses which were based on mothers’ age and home locations as factors affecting EBF at ∝ level of 0.05. The findings of this study revealed that there is no significant difference in the knowledge, and practice of EBF among mothers based on their age in Dutsin-Ma, community (P=0.426>0.05) and (P=0.452>0.05) respectively. There is no significant difference in the knowledge of EBF among mothers in Dutsin-Ma community based on their home location (P=0.286>0.05). Meanwhile, there is significant difference in the practice of EBF among mothers in Dustin-Ma community based on their home location (P=0.001<0.05). Following the findings of this study, it is concluded that young and old mothers did not differ in the knowledge, and practice of EBF in Dutsin-Ma community. They also did not differ in the knowledge of EBF based on their home locations, but they differ in the practice based on their home location. Finally, it is recommended that mothers should be encouraged to control any factor capable of deterring them early initiative of breastfeeding (i.e. after an hour from birth) up to the first six months of their infants’ life in exclusion of any other formula even water besides prescribed drugs.